PENGARUH APLIKASI SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) DAN PELAYANAN AKTA KELAHIRAN TERHADAP KEPUASAN MASYARAKAT DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN PEKALONGAN - Pricilia Dwi Candra; Hesti Lestari (Journal of Public Policy and Management Review, 2018)
Public service system that existed in Indonesia, in practice many are yet to establish the standard services such as the clarity of fees, procedures, requirements, service time so a lot of the public who use the services of touts as done the community in the manufacture of a birth certificate in the Office of the Department of population and civil registration Pekalongan. Improvement of public service continues to be done in order to get a quality service to generate a community satisfaction, as done by the civil registration Department of population and Pekalongan that have implemented innovation application of SIAK based online so that the related parties can access without having to come to the Office of. This research aims to analyze the effect of the application of SIAK and Ministry birth certificate toward the satisfaction of Society in the service of the population and civil registration Pekalongan, using the theory of public administration, management public services, management information systems, and community satisfaction. These studies use quantitative methods involving 100 respondents, namely the community encountered directly during the processing to make a birth certificate. Based on the results of research, the application of SIAK and Ministry birth certificate has an impact on the satisfaction of the community i.e. amounting to 12.7%. Whereas the application of SIAK and simultaneous birth certificate service to the satisfaction of the community. The authors give recommendations do the existence of repair home network or server on the application so that it does not suffer the SIAK error, and the addition of an employee to the employee shortage areas.